Classification and Identification Model of Young Women's Torso Shape Based on Human Surface Curve Features (Journal of Fiber Bioengineering and Informatics, 2023)
Human body shape analysis is an important reference basis for garment sizing and modification. Thestudy of human body shape is to better master the relationship between the size and shape of differentbody parts and the overall shape of the garment. In this paper, 245 young women aged between 18 and24 years in school in northern China were selected as the study subjects by applying the 3D human bodymeasurement technology. Using the statistical software SPSS, principal component analysis, correlationanalysis and R-type clustering were performed to evaluate 16 variables, including height, girth, and bodysurface angles. Five body angles were extracted as classification indexes: chest angle, back inclination,dorsal angle, body lateral angle, and buttocks angle. These indexes were critical in explaining thecharacteristics of the torso surface curve. Consequently, the body types were divided into three categoriesusing K-means clustering. More detailed characteristics of the eight body types ${\rm Y}_{{\rm II}}$ to ${\rm B}_{{\rm III}}$ were classifiedby combining the chest-waist drop of the Chinese National Standard classification indication. Thenaccording to the classification results, a recognition template that can automatically classify body shapewas created through the Baidu AI EasyDL development platform. Experimental results showed thatthe average precision of the body type recognition model reached 91.7%, among which the recognitionaccuracy for Type III S body shape was over 95%, providing a meaningful reference for body typeclassification research.